Issues and Challenges in Political Engagement of Women in Pakistan: A Narrative Study Of Women Activist Groups - Tariq, Maahum; Ahmed, Umair; Warraich, Saqib Khan (Annals of Human and Social Sciences, 2023)
This study aims to analyze women's engagement in activism and political participation in Pakistan, with a particular focus on women who identify themselves as members of liberal or conservative groups. It explores their perspectives on Feminism and Nationalism, with religious affiliations as a significant factor. In the present study, employing a qualitative approach, 16 women participants aged 23 to 48 were interviewed. The study reveals distinct gender roles and feminist ideology perceptions between the two groups, closely intertwined with Islamic beliefs. Liberal women emphasize women's active public participation, challenging religious fundamentalism. In contrast, conservative women, identifying as nationalists and antifeminists, prefer women's involvement in the private sphere, embracing Islamic feminism less. Liberal respondents express dissatisfaction with Pakistan's sexist culture and challenges in advocating for gender equality. The study's implications extend to gender equality, female identity within nationalism, women's public involvement, and the impact of biases on challenging societal gender role expectations. In the context of feminism and nationalism, this study sheds light on the impact of religious beliefs on the viewpoints of socially and politically engaged women in Pakistan, offering valuable insights for academics and professionals.